2009
DOI: 10.3109/13682820802381334
|View full text |Cite
|
Sign up to set email alerts
|

Why do speech and language therapists stay in, leave and (sometimes) return to the National Health Service (NHS)?

Abstract: Whilst some preferences appear to require increased resources, others such as reducing bureaucracy and valuing professionals do not. The full impact of Agenda for Change has yet to be established. Predicted excess labour supply of allied health professionals and future structural changes present pressures but also possible opportunities for speech and language therapists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Despite these complaints, very few (13%) said that they would not be an SLT in 5 years’ time. Rossiter (2008) also found a high level of retention and Loan‐Clarke et al (2009) found that the profession offers job security, pension and opportunities for professional development which add to the rewards of the work. A further factor may be that the profession is flexible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these complaints, very few (13%) said that they would not be an SLT in 5 years’ time. Rossiter (2008) also found a high level of retention and Loan‐Clarke et al (2009) found that the profession offers job security, pension and opportunities for professional development which add to the rewards of the work. A further factor may be that the profession is flexible.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Vallino‐Napoli and Reilly (2004) found that Australian therapists valued research and that most were aware of evidence‐based practice, but that lack of time prevented them from using evidence or contributing to research. Others have looked at the recruitment and retention of SLTs and their job satisfaction and career progression (American Speech–Language–Hearing Association (ASHA) 2008, Loan‐Clarke et al 2009, Rossiter 2008). Findings are of a high level of retention encouraged by the positive nature of the work, job and pension security, and the opportunities for training and career progression.…”
Section: Introductionmentioning
confidence: 99%
“…One result of restructuring, mentioned in the qualitative comments by some respondents, had been that jobs for professionspecific heads of AHP services have increasingly been lost. We have suggested (Loan-Clarke et al, 2009) that AHPs need to be proactive in restructuring activity in order to influence the shape of AHP services in the future. Greater influence/control over their own activities could make retention and return a more attractive proposition for AHPs.…”
Section: Discussionmentioning
confidence: 99%
“…analysis to explore open-ended items, with one of these (Loan-Clarke et al, 2009) quantifying the data to perform frequency distribution analysis. One qualitative study identified themes within the data collected from interviews, which they then coded; the other used phenomenological analysis to interpret findings.…”
Section: Studies Includedmentioning
confidence: 99%
“…Only one (Warden et al, 2008) stated the methodological orientation that underpinned the study. The two mixed methods papers that gathered qualitative data through large-scale surveys (Heritage, Quail & Cocks, 2018;Loan-Clarke, et al, 2009) did not lend themselves well to the COREQ criteria, with some items being irrelevant. Of the fourteen criteria that were relevant to both, nine were met in each case.…”
Section: Quality Appraisalmentioning
confidence: 99%